The Role of Work Motivation and Job Satisfaction in Creating Employee Performance (Study on Permanent Lecturers of STIE Indonesia Banking School) - Santi Rimadias; Ossi Ferli; Fajar Hertingkir (Jurnal Ilmu Manajemen & Ekonomika, 2016)
This research aims to determine the role of work motivation (intrinsic and extrinsic factors) and job satisfaction as an employee performance maker on STIE Indonesia Banking School permanent lecturers. The population in this study were all STIE Indonesia Banking School permanent lecturers in 2015. We conducted a survey and the respondents was taken from STIE Indonesia Banking School permanent lecturers for 31 respondents. We used questionnaire method to collect information from the respondents. Data were analyzed using Partial Least Square (PLS) with Smart PLS 3.0 software. The results showed that intrinsic factors and extrinsic factors has a positive effect on job satisfaction, furthermore intrinsic factors has a positive effect on employee performance. Whereas extrinsic factors and job satisfaction has no effect on employee performance.